Microwave Synthesized Three-dimensional Hierarchical Nanostructure CoS2/MoS2 Growth on Carbon Fiber Cloth: A Bifunctional Electrode for Hydrogen Evolution Reaction and Supercapacitor. (10th September 2016) - Su, Can; Xiang, Jianyong; Wen, Fusheng; Song, Laizhou; Mu, Congpu; Xu, Dongyang; Hao, Chunxue; Liu, Zhongyuan
Graphical abstract: Abstract: In this work, we demonstrate the synthesis of three-dimensional hierarchical nanostructured cobalt disulfide/molybdenum disulfide growth on carbon fiber cloth (CoS2 /MoS2 /CC) for hydrogen evolution reaction and supercapacitor. CoS2 nanoparticles anchor on flower-like MoS2 nanosheets grown on CC by a two-step procedure via facile single mode microwave-assisted hydrothermal technique. It was observed that CoS2 /MoS2 nanocomposites were uniformly dispersed on CC and CoS2 nanoparticles were wrapped by flower-like MoS2 nanosheets. Remarkably, the binder-free CoS2 /MoS2 /CC maintains its activity after 1000 cycles and exhibits superior catalytic activity in hydrogen evolution reaction, with a low overpotential of 177 mV to achieve current density of 10 mA cm −2 and a Tafel slope of 66 mV dec −1 . Furthermore, the bifunctional CoS2 /MoS2 /CC for supercapacitor delivers a higher specific capacitance of 406 F/g and excellent long-life cycling stability, retaining 95.27% of the initial capacitance after 10000 cycles. The enhanced hydrogen evolution reaction and supercapacitor property may be ascribed to the synergistic effect between metallic CoS2 and MoS2, moreover more electrochemical accessible active sites and fast electron transport path can be obtained.